Analisis Kemampuan Penalaran Matematis Pada Materi Operasi Hitung Campuran Sebagai Implementasi Dalam Kehidupan Sehari-Hari Siswa Kelas VI Sekolah Dasar Di Desa Larikrejo - Riswari, Lovika Ardana; Sari, Aulia Candra; Suryanto, Halim (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Mathematics and mathematical reasoning cannot be separated, mathematical reasoning is an ability that students must have in the process of solving mathematical problems both in learning and in everyday life. The purpose of this study was to find out and analyze students' mathematical reasoning abilities using mixed arithmetic operations in everyday life. The method used in this study is based on descriptive qualitative, by giving questions to students of grade VI which are then answered by students. From the questions that have been done by 5 grade VI students, the results obtained with the creteria (very good) are obtained by 1 student, (good) are obtained by 2 students, (sufficient) are obtained by 1 student, and (less) are by 1 student. The results of the study showed that the mathematical reasoning abilities in class VI in Larikrejo Village developed quite well.